UHPLC-ESI-QTOF-MS/MS Profiling of Phytochemicals from Araticum Fruit (Annona crassiflora Mart.) and Its Antioxidant Activity - Henrique Silvano Arruda; Célio Fernando Figueiredo Angolini; Marcos Nogueira Eberlin; Glaucia Maria Pastore; Mario Roberto Marostica Junior (Foods, 2023)
Araticum is a native species of the Brazilian Cerrado with a high potential for exploitation. Several studies have stated that araticum is a rich source of phytochemicals with multifaceted biological actions. However, little information is available regarding the characterization of phytochemicals found in the pulp of this fruit. In this context, this study aimed to carry out a comprehensive characterization of phytochemicals present in the araticum pulp using ultra-high-performance liquid chromatography coupled to a quadrupole time-of-flight mass spectrometer (UHPLC-ESI-QTOF-MS/MS). The antioxidant potential of araticum pulp was also evaluated. UHPLC-ESI-QTOF-MS/MS profiling of the phytochemicals allowed for the identification and annotation of 139 phytochemicals, including organic acids, jasmonates, iridoids, phenolic compounds, alkaloids, annonaceous acetogenins, fatty acid derivatives, and other compounds. Among them, 116 compounds have been found for the first time in araticum pulp. Phenolic compounds and their derivatives represented about 59% of the phytochemicals identified in the extract. Moreover, araticum pulp showed high total phenolic compound content and antioxidant activity. The majority of identified phytochemicals have been associated with key roles in the plant’s defense mechanisms against biotic and abiotic stress factors in the Cerrado environment. Furthermore, many of these phytochemicals found in the araticum pulp are already widely recognized for their beneficial effects on human health. Our findings showed that the araticum fruit contains different classes of phytochemicals that exert various biological activities, both in the plant itself and in humans.